Adenomatoid odontogenic tumor: an unusual histological presentation with - Cunha, John Lennon Silva; Silva, Amanda Feitoza da; da-Fonte, Juliana Batista Melo; Rocha, Raimundo Silva; de-Melo, Maria de Fátima Batista; Albuquerque-Júnior, Ricardo Luiz Cavalcanti de (Journal of Oral Diagnosis, 2018)
Adenomatoid odontogenic tumor (AOT) is a relatively rare odontogenic tumor derived from odontogenic epithelium. Although there have been many reports regarding the histo- logical spectrum of AOT, only a few have highlighted unusual histological presentations. A 28-year-old female presented with a painless swelling in the maxillary anterior region. Radiological examinations revealed a well-defined unilocular lesion, with sclerotic margins, containing foci of slightly radiopaque material and promoting root divergence between teeth 22 and 23. An incisional biopsy showed spindle-shaped cells forming sheets, strands, and whorled masses, together with ductlike structures, throughout a scanty fibrous stroma. In some areas, sheets of polyhedral epithelial cells with prominent intercellular bridges, mild pleomorphism, and droplets of amyloidlike material were observed. The diagnosis was AOT with “Pindborg-like” differentiation. The occurrence of such differentiation in AOT seems to represent the caricatures of the enamel organ itself and is believed to be an altered phenotype of the tumor.